Diagnostic Performance of Western Blot for Congenital Toxoplasmosis: A Systematic Review and Meta-Analysis - Sebastián Serna Rivera; Maria Antonia Restrepo Duque; Jocelyn Arredondo Torres; Juan David Fandiño; Luis Felipe Mosquera; Jorge Enrique Gomez Marin (International Journal of Medical Students)
Background: Congenital toxoplasmosis results from infection with the parasite Toxoplasma gondii, which is transmitted from mother to child during pregnancy. Although Western blot is considered the most sensitive diagnostic tool for congenital toxoplasmosis, its diagnostic performance has not been subjected to meta-analysis.